Non-alcoholic fatty liver disease in chronic hepatitis B patients Reply - Ceylan, Bahadır; Arslan, Ferhat; Batırel, Ayşe; Fıncancı, Muzaffer; Yardımcı, Cem; Fersan, Esra; Paşaoğlu, Esra; Yılmaz, Mesut; Mert, Ali (Aves, 2016)
[Abstract Not Available]
WOS: 000382747100018
Keywords: Non-Alcoholic; Fatty Liver; Disease in Chronic; Hepatitis B Patients